Innovations, algorithms, and applications in cognitive informatics and natural intelligence - Chui, Kwok Tai 1991-; Lytras, Miltiadis D. 1973-; Liu, Ryan Wen 1987-; Zhao, Mingbo 1982- (IGI Global, 2020)
"This book explores innovations, algorithms, and applications in cognitive informatics and natural intelligence"--
"Premier Reference Source."
Description based on title screen (IGI Global, viewed 02/15/2020)
Keywords: Cognitive science; Computational intelligence